Periventricular nodular heterotopias is associated with mutation at the FLNA locus-a case history and a literature review - Lin Yang; GuangSheng Wu; HuiMei Yin; MengLan Pan; YaFei Zhu (BMC, 2023)
Abstract Background Periventricular nodular heterotopia (PNH), associated with FLNA mutations, is a rare clinical condition potentially associated with multiple systemic conditions, including cardiac, pulmonary, skeletal, and cutaneous diseases. However, due to a paucity of information in the literature, accurate prognostic advice cannot be provided to patients with the disease. Case presentation We report a 2-year-old female whose PNH was associated with a nonsense mutation in the q28 region of the X chromosome, in exon 31 of FLNA (c.5159dupA). The patient is currently seizure-free and has no congenital heart disease, lung disease or skeletal or joint issues, and her development is normal. Conclusions FLNA-associated PNH is a genetically-heterogeneous disease, and the FLNA mutation, c.5159dupA (p.Tyr1720*) is a newly identified pathogenic variant. FLNA characterization will help the clinical diagnosis and treatment of PNH and provide individualized genetic counseling for patients.